The hype of social capital in the finance-growth nexus - Ibrahim Dolapo Raheem; Kazeem Bello Ajide; Xuan Vinh Vo (African Governance and Development Institute (AGDI), 2021)
The trilogy among economic growth, social capital (SC), and financial development is exami ned based on three hypotheses: first, SC is important in the finance-growth nexus. Second, th ere is a threshold effect of SC in the finance-growth nexus. Third, the SC-finance-growth tril ogy depends on the countries' income level. Building dataset for 70 countries,someinteresting results were obtained: (i) the marginal effects of both SC and finance promotes economic gro wth at higher levels; (ii)there is evidence of a threshold effect of SC, as finance enhances mor e growth when SC is below the threshold level; (iii) higher-income countries tend not to bene fit from the SC-finance-growth trilogy. These results suggest that the influence of SC on gro wth trajectory is exaggerated in the literature. The study recommends that policymakers shoul d pursue other sources of economic growth aside SC, while ensuring that the level of SC does not deteriorate.
Keywords: O43; G20; 330; Economic growth; Financial development; Social capital; Threshold effect